Appearance of Tumor Vessels in Patients With Choroidal Osteoma Using Swept-Source Optical Coherence Tomographic Angiography - Zhou, Nan; Xu, Xiaolin; Liu, Yueming; Wei, Wenbin; Peng, Xianzhao (Frontiers in Oncology, 2021)
Objective To report the morphologic characteristics of tumor-related vasculatures and their association with secondary choroidal neovascularization (CNV), subretinal fluid (SRF), choroidal thickness, retinal pigment epithelium (RPE) alterations, subretinal hemorrhage, and tumor decalcification in eyes with choroidal osteoma (CO), using swept-source optical coherence tomographic angiography (SS-OCTA). Design Cross-sectional observational study. Participants We included 26 patients recruited from Beijing Tongren Hospital with a diagnosis of CO, based on the presence of yellow-orange mass deep to the RPE under indirect ophthalmoscopy and occupying the choroid with well-defined margins and bone density on ultrasonography or computed tomography and focal hyperfluorescent spots with no homogeneous pattern on fluorescein angiography/indocyanine green angiography (FA/ICGA). Data were collected from April 1, 2020, to April 1, 2021, and analyzed from April 30 through May 30, 2021. Methods Applying SS-OCTA systems operating at 1,050-nm wavelengths, eyes with CO were imaged. Main Outcome and Measures Tumor-related vasculature in eyes with CO was characterized using multimodal imaging that included fundus photography, FA/ICGA, SS-OCT, and SS-OCTA, and the images were anatomically aligned. CO thickness was manually measured as the distance between the upper boundary of the tumor and the underlying sclerochoroidal interface on the SS-OCT images. Subfoveal choroidal thickness was manually measured as the distance between the Bruch membrane and the sclerochoroidal interface on the SS-OCT images. Results Of the 26 Asian patients, 16 (62%) were women and 10 (38%) were men. The mean age was 26.8 years (median, 23; range, 8–45 years), and the mean best corrected visual acuity (BCVA) was 20/40. Thirty-three eyes underwent imaging and were diagnosed with CO. Indocyanine green angiography identified inhomogeneous hyperfluorescence due to tumor-related vasculature, and all corresponded to the structures that appeared as sea-fan vascular networks (SFVNs) combined with clusters of tangled vessels on SS-OCTA images. SFVNs were detected on SS-OCTA imaging in all eyes (100%), terminal tangled vascular structures in 32 of 33 eyes (97%), but not identified on ICGA. Of the 33 tangled vascular structures, 32 (97%) were located at the edge of or inside the tumor, and only 1 (3%) was associated with type 2 neovascularization. In addition, SS-OCT revealed SRF in 33 eyes (100%), 33 (100%) were located at the edge of CO, and only 1 was underlying macular. SRF with retinal edema was seen in 30 of 32 eyes (94%). Conclusions In eyes with CO undergoing SS-OCTA imaging, tumor-related vasculature appears as SFVNs combined with tangled vascular structures or few type 2 neovascularization. The identification of actual tumor vasculature in patients with CO as SFVNs with inner or terminal vascular tangles rather than previously described CNV may help facilitate understanding of their pathogenesis, tumor control, and response to treatment.